Frequency of bovine cysticercosis in the state of Rondônia, Brazil - Guimarães-Peixoto, Rafaella P.M.; Franco, Camila; Pinto, Paulo S.A.; Rossi, Gabriel A.M.; Cruz, Breno C. [UNESP]; Gomes, Lucas V.C. [UNESP]; Felippelli, Gustavo [UNESP]; Teixeira, Weslen F.P. [UNESP]; Soares, Vando E.; Couto, Luiz Felipe Monteiro; Bastos, Thiago S.A.; Apolinário, Paula F.; et al. (Elsevier, 2020)
Bovine cysticercosis remains as one of the most important cause of carcasses and viscera condemnation in Brazilian slaughterhouses. However, the efficiency of post-mortem inspection for the diagnosis of this zoonotic disease is relatively low, and few available studies were performed through serological exams. This study evaluated the frequency of bovine cysticercosis in cattle herds located in different farms of the state of Rondônia, Brazil. Among the 987 animals slaughtered from 33 farms, 21 animals (Frequency: 2.13%; 95C.I. 1.23–3.03) were considered as positive through indirect ELISA and confirmed by Immunoblot tests and the cysticercosis was detected in 12 farms (36.36% - C.I. 95% 19.95–52.78). The disease was detected in the municipalities Vale do Paraíso (12.50%), Theobroma (8.11%), Guaporé (7.27%), Rolim de Moura (5.71%), Presidente Médici (5.0%), Ouro Preto do Oeste (4.69%), Nova União (1.77%), Nova Brasilândia d'Oeste (1.14%) and Ministro Andreazza (1.01%). Therefore, prophylactic measures should be taken to improve beef production, control bovine cysticercosis and reduce costs to public health in this Brazilian state.
Keywords: Epidemiology; Immuboblot; Indirect ELISA; Taenia saginata